ToLCNDV-ES infection in tomato is enhanced by TYLCV: Evidence from field survey and agroinoculation - Vo, Thuy Thi Bich; Troiano, Elisa; Lal, Aamir; Hoang, Phuong Thi; Kil, Eui-Joon; Lee, Sukchan; Parrella, Giuseppe (Frontiers in Microbiology, 2022)
The tomato leaf curl New Delhi virus (ToLCNDV), a bipartite begomovirus (family Geminiviridae), poses a significant threat to various horticultural crops in many Asian and Mediterranean countries. Since its identification, the Asian strain of this virus has exhibited severe infectivity and caused high yield loss in tomato and cucurbit production in the Indian subcontinent and other parts of Asia. ToLCNDV-ES, a different strain of ToLCNDV, emerged recently in the Mediterranean Basin and caused significant outbreaks in Cucurbitaceae species but has shown low adaptation to tomatoes. In a field survey, tomato plants infected with this Mediterranean strain were not discovered. Nevertheless, the same field survey revealed that ToLCNDV-ES occurred in natural double infection with tomato yellow leaf curl virus (TYLCV) in tomato plants with an infection ratio of up to 50%. Moreover, results obtained from experiments where tomato plants agro-inoculated simultaneously with infectious clones of ToLCNDV-ES and TYLCV showed that ToLCNDV-ES was detected in tomatoes while synergized with TYLCV with infection ratios similar to those found under field conditions. Quantitative PCR data indicated the highest amount of ToLCNDV in co-infected plants and no significant change in TYLCV titers among the different mixed infections. Moreover, it was ascertained that not all begomoviruses can enhance the infectivity of Mediterranean ToLCNDV isolates in tomato plants. Our study reports a new finding regarding the ToLCNDV-ES response in tomato while synergized with TYLCV with evidence from both field and laboratory conditions